Identification of Teak [tectona grandis L] Plantations Using Multi-temporal Landsat MSS Data - Srivastava, V. K; Oza, M. P. (Indian Forester, 1991)
Multi-temporal, Landsat Multi Spectral Scanner (MSS), digital data have been used to select a proper season and month for identification of teak (Tectona grandis L.) plantations. Multldate satellite data used were corrected to improve the geometric and radiometric fidelity amongst the data sets. The radiance values of in the four Landset MSS bands were used to calculate normalized difference vegatation index (NDVI) for teak discrimination from other natural forest types growing In Vellapur Forest Division, Karnataka, India. It was found that the teak plantations could be properly identified In the month of March when trees are leafless. This observation was further supported by divergence analysis. The maximum value ot minimum divergence was observed for March data. This implies that the land cover classes can be better separated using March data in comparison with other data (October, January and April).